2017
DOI: 10.37358/mp.17.3.4885
|View full text |Cite
|
Sign up to set email alerts
|

Using Polypropylene for Bronchial Stump Closure After Pulmonary Resections

Abstract: The bronchial stump fistula shown by patients undergoing adjusted pulmonary resections is an extremely severe condition affecting the prognosis of this patients. Within our study, we have used an innovative technique of closing the bronchial stump for 38 patients undergoing adjusted pulmonary resections. The suture of the bronchial stump was made through an innovative method, by practicing the suture with isolated 2.0 Prolene wires armed with patches of Polypropylene. The incidence of the bronchial stump fistu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…The results of our study confirm the results of other authors in the literature who observed that after the laparoscopic approach of the inguinal hernia, the incidence of postoperative pain as well as the need for analgesic medication is lower compared to instances where surgical treatment of hernia was practiced using a classic approach [6,7].…”
Section: Resultssupporting
confidence: 89%
“…The results of our study confirm the results of other authors in the literature who observed that after the laparoscopic approach of the inguinal hernia, the incidence of postoperative pain as well as the need for analgesic medication is lower compared to instances where surgical treatment of hernia was practiced using a classic approach [6,7].…”
Section: Resultssupporting
confidence: 89%
“…The results showed a benefit of reduced hemodynamic decompensation in some patients, but at the cost of an increased rate of major and intracranial bleeding events, that overweighed the total benefit. These findings were confirmed in other subsequent meta-analyses [9][10][11][12] and they raise the question that, if improved risk classification criteria for these patients could identify which of them are at higher risk, then the risk-benefit ratio could improve in favor of the more aggressive therapies.…”
Section: Resultsmentioning
confidence: 53%
“…But these symptoms were transient in all cases. A plausible explanation for these symptoms is that in most cases this is the first time in these students' lives that they come in contact with the body of a deceased person and become aware of the consequences of death, which leads to anxiety [15,16]. In our study 70.55% of the respondents had their first contact with the body of a deceased person during the anatomy course.…”
Section: Resultsmentioning
confidence: 67%